2020
DOI: 10.1016/j.jvs.2019.05.011
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review and meta-analysis of endovascular versus open surgical repair for the traumatic ruptured thoracic aorta

Abstract: Objective: The purpose of this study was to compare clinical outcomes between open repair and thoracic endovascular aortic repair (TEVAR) in traumatic ruptured thoracic aorta. Methods: A comprehensive search was undertaken of the four major databases (PubMed, Embase, Scopus, and Ovid) to identify all published data comparing open vs endovascular repair. Databases were evaluated to July 2018. Odds ratios (ORs), weighted mean differences, or standardized mean differences and their 95% confidence intervals (CIs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 47 publications
0
17
0
2
Order By: Relevance
“…EVAR has been the first-line treatment for TAI according to the guidelines of the Society for Vascular Surgery (SVS) [2], the European Society of Cardiology [9], the Eastern Association for the Surgery of Trauma [10], and the European Society for Vascular Surgery (ESVS) [1], considering previously published reports of the low mortality and morbidity of EVAR compared with open surgery. Several studies including a relatively large number of cases with a long follow-up showed satisfactory outcomes of EVAR for TAI and superiority of EVAR over open surgery [3,5,6,[11][12][13]. However, EVAR for TAD was scarcely reported, and the characteristics of TAD were not thoroughly known.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…EVAR has been the first-line treatment for TAI according to the guidelines of the Society for Vascular Surgery (SVS) [2], the European Society of Cardiology [9], the Eastern Association for the Surgery of Trauma [10], and the European Society for Vascular Surgery (ESVS) [1], considering previously published reports of the low mortality and morbidity of EVAR compared with open surgery. Several studies including a relatively large number of cases with a long follow-up showed satisfactory outcomes of EVAR for TAI and superiority of EVAR over open surgery [3,5,6,[11][12][13]. However, EVAR for TAD was scarcely reported, and the characteristics of TAD were not thoroughly known.…”
Section: Discussionmentioning
confidence: 99%
“…Endovascular aortic repair (EVAR) offers lower perioperative mortality and provides satisfactory outcomes compared with open repair in patients with TAI [5,6]. It has been recommended as the first-line treatment by the 2011 Society for Vascular Surgery clinical practice guidelines and the 2017 European Society for Vascular Surgery Guidelines [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Endovascular repair provides benefit as it avoids major surgical incisions, aortic cross-clamping, reduces procedural time, decreases blood loss, and decreases end-organ ischaemia. (Dangas et al, 2012 ; Walsh et al, 2008 ) Reduced post-operative mortality (30 day; 7.9% vs 20% and 1 year; 8.7% vs 17%), in addition to reduced procedural complications, have also been demonstrated in those undergoing TEVAR compared with open repair (Harky et al, 2020 ; Hsieh et al, 2019 ). Despite these benefits, meta-analyses have shown TEVAR to be associated with pooled reintervention rates of 15%; reasons including, endoleak (33.2%), false-lumen perfusion and aortic dilation (19.8%), and new dissection (6.9%).…”
Section: Introductionmentioning
confidence: 99%
“…6 The literature regarding this topic is incomplete and outdated. 7 Available studies were mainly performed in countries with different emergency medical systems from those in Europe. Only one large retrospective study has been performed in Europe (Germany), where pre-hospital care might include a physician on site.…”
Section: Introductionmentioning
confidence: 99%